As execuções fiscais baseadas em débitos agrários renegociados através da Lei n. 9.138/95 - Meira, Tales Dias de (Universidade do Vale do Rio dos Sinos, 2019)
This dissertation aims to analyze the problem of tax executions based on agricultural debts renegotiated with the Law No. 9.138/95. Faced with the effectiveness of Provisional Measure No. 2.196-03/01, the rural credits arising from the renegotiations made on the basis of the above Law were transferred to the Federal Government. Therefore, debts originating from rural financing made between private financial institutions and their borrowers have been given a new guise, since the private character of the debt turned into public character. In this way, a comparative approach will be made between the legal nature of private and public credits so that, in a second moment, the conversion of private debt into public debt caused by the validity of the Provisional Measure can be addressed. Subsequently, the problem of converting private credits into public credits will be discussed in the light of constitutional and infraconstitutional provisions in the Brazilian legislation. This study makes use of the deductive method, starting from theoretical and doctrinal concepts and their practical applications. Thus, the research shows the importance of critically observing the transfer of private rural credits to the Federal Government enabled by the Measure No. 2.196-03/01.
Keywords: Crédito rural; Crédito privado; Crédito Público; Medida Provisória N. 2.196-03/01; Legislação infraconstitucional; Constituição Federal; Rural credit; Private credit; Public credit; Provisional Measure No. 2.196-03/01; Infraconstitutional legislation; Federal Constitution; ACCNPQ::Ciências Sociais Aplicadas::Direito